Performing Some Offensive and Defensive Skills in Relation to the Multidimensional Anxiety of ALtadamon Basketball Players - Mutair Hamidi Al Karizi, Ali; Abdul Jabbar Murad, Imad; Mutair Hamidi Al-Karizi, Maytham (International Journal of Psychosocial Rehabilitation, 2020)
The present research aims to identify the level of multi-dimensional anxiety and evaluate the performance of some offensive and defensive skills of advanced players in Hilla basketball club and to identify the nature of the relationship between multidimensional anxiety and the performance of players ALtadamon advanced basketball. the researcher used the descriptive method of survey methods and case study, included A sample of the research on the players of the Altadamon Club (14) basketball applicants. Using the statistical bag (SPSS), the research came up with a set of conclusions, including the reduction of multidimensional anxiety in the players. One of the most important recommendations is to emphasize the importance of studying multidimensional anxiety as a personal situation whose responses affect the athlete and to determine the influential dimension in performance.